Endoscopically-assisted operations in the treatment of odontogenic peripheral osteomyelitis of the posterior mandible. Issue 5 (June 2016) - Huang, Zixian; Huang, Zhiquan; Zhang, Daming; Hu, Huijun; Liang, Qixiang; Chen, Weiliang
Abstract: The aim of this study was to evaluate the possibility of using an endoscope in the treatment of five patients with odontogenic peripheral osteomyelitis of the posterior mandible diagnosed between March 2012 and September 2014. After imaging and general preoperative examination, the patients had endoscopically-assisted curettage and sequestrectomy. The data collected included the duration of the operation, complications, and patients' degree of satisfaction. The mean duration of the operation through an intraoral incision, was 46 (range 40-60) minutes. Patients were followed up at 1 week, 3 months, and 6 months, with no signs of recurrence. One patient reported postoperative swelling in the mandibular angle but this settled. The incision was minimal and left no postoperative scar on the face. All the patients recovered free of complications and were satisfied with the results of the operation. Because of the minimally-invasive intraoral incision, endoscopically-assisted treatment of odontogenic peripheral osteomyelitis of the posterior mandible can maintain external facial integrity without surgical scars.